Gerechte Waffen und die Kunst des Strafens - Höckelmann, Michael (Monumenta Serica - Journal of Oriental Studies, 2010)
In China, as in the West, philosophers have asked questions about how to legitimize warfare. One text, the Lüshichunqiu呂氏春秋, compiled around 240 B.C. in the state of Qin 秦, offers a solution in terms of “righteous weapons” (yibing義兵), often translated as “just war” by Western scholars. However, yibingdoctrine differs from Western theories of bellum iustumin certain respects: First, the yibingare embedded in the calendar and its cosmology of five phases (wuxing 五行), in which they, together with domestic punishments, represent the “recessive” powers of yin陰. Second, because warfare is the natural state of human beings, which only the emergence of political authority and the imposition of punishments could curtail, the yibingwere an extension of domestic penal laws and other penal practices onto the international level. Third, yibingare elicited by the improper punishments of the legal ruler in an opposing state, hence yibingare a tool for a ruler to save his own people. The theory of yibingin the Lüshichunqiuis more than propaganda legitimizing Qin’s conquest of the other six “warring states”, but constitutes a highly complex theory about law, punishment, the calendar and cosmological warfar